Cardioneuroablation for Treating Vasovagal Syncope: Current Status and Future Directions - Le Li; Sunny Po; Yan Yao (Arrhythmia & Electrophysiology Review)
Syncope is defined by transient and spontaneous loss of consciousness with rapid recovery. Vasovagal syncope (VVS) is the most common form of syncope and is strongly associated with hypervagotonia. There is, however, a lack of effective therapies for VVS. Cardioneuroablation (CNA) is an emerging and promising intervention for VVS with favourable outcomes. CNA has been shown to suppress excessive excitation of vagal activity through ablating the cardiac ganglionated plexi. CNA in the management of VVS requires more structured and comprehensive studies and several issues concerning patient selection, selection of ablation targets, ablation endpoints and the long-term effect of CNA are yet to be determined. This review describes its clinical applications and future directions based on current research data and the authors’ own experiences.